Pengaruh Karakteristik Wirausaha, Modal Usaha, Strategi Pemasaran terhadap Perkembangan UMKM Kota Padangsidimpuan - Nursalamah .; Pertama Yul Asmara Pane; Ade Maya Mei Shanty (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting economic growth, creating employment opportunities, increasing community income, and strengthening regional economies. However, the development of MSMEs continues to face various challenges influenced by entrepreneurial characteristics, business capital, and marketing strategies. Understanding the influence of these factors is essential for developing effective policies and strategies to improve the competitiveness and sustainability of MSMEs.This study aims to analyze the influence of entrepreneurial characteristics, business capital, and marketing strategies on the development of MSMEs in Padangsidimpuan City.This study employed a quantitative approach using a survey research design. The population consisted of MSME owners in Padangsidimpuan City, with a sample of 100 respondents selected through purposive sampling. Primary data were collected using a structured questionnaire based on a five-point Likert scale. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) through multiple linear regression analysis to examine the effect of the independent variables on MSME development.The results indicate that entrepreneurial characteristics have no significant effect on MSME development, with a significance value of 0.105 (>0.05). In contrast, business capital has a significant effect with a significance value of 0.030 (<0.05), while marketing strategy has a positive and significant effect with a significance value of 0.000 (<0.05). Furthermore, the coefficient of determination (R Square) of 0.516 indicates that the three independent variables explain 51.6% of the variation in MSME development, whereas the remaining 48.4% is explained by other factors outside the research model.Based on these findings, it can be concluded that the development of MSMEs in Padangsidimpuan City is more strongly influenced by business capital and marketing strategies than by entrepreneurial characteristics. Therefore, improving access to business financing and enhancing the ability of MSME owners to implement effective marketing strategies are essential to support sustainable business development and strengthen the competitiveness of MSMEs.